THE EFFECTIVENESS OF FINGERHOLD RELAXATION TECHNIQUE AND SPIRITUAL EMOSIONAL FREEDOM TECHNIQUE (SEFT) TO THE PAIN INTENSITY SCALE ON PATIENTS WITH POST CAESAREAN SECTION - Atun Raudotul Ma’rifah; Rahmaya Nova Handayani; Pramesti Dewi (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2018)
Post caesarian section pain can cause physical and psychological effects to mothers. The pain can be reduced with pharmacological or non-pharmacological pain management. One of the pharmacological techniques is fingerhold relaxation and spiritual emotional freedom technique (SEFT). The study aimed to discover the effectiveness of fingerhold relaxation and SEFT to pain intensity of post caesarean section. This study was categorized into quasi-experiment research with two groups comparison pre-test and post-test design. The samples were 45 respondents comprising of 15 respondents for experimental group using SEFT, 15 for experimental group using fingerhold relaxation, and 15 for control group . The data was analyzed using regression linier test. The result showed that the correlation value of control group was 0,431 with R-Squere 18,6 %. Meanwhile, in experimental group with fingerhold relaxation, the correlation value was 0.671 and R-square value was 45%. Furthermore, the correlation value of experimental groups using SEFT was 0.874 and R square was 76%. In conclusion, SEFT is effective to decrease the pain on patient with post caesarean section. Therefore, nurses are required to help mothers to feel comfortable in controlling the pain of post caesarean section.Keywords: caesarean section, finggerhold, pain, SEFT